The effect of transforming growth factor beta 1 (TGF-beta 1) on the regenerate bone in distraction osteogenesis - A biomechanical, histologic and immunohistochemical study on rabbits - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2007)
Distraction osteogenesis is a well established clinical treatment for limb length dicrepancy and skeletal deformities. Transforming growth factor beta 1 (TGF-beta 1) is a multifunctional peptide which controls proliferation and expression of cells specific to bone like chondrocytes, osteoblasts, osteoclasts including mesenchymal precursor cells. To decrease the external fixation time with increasing the strength of regenerate ( newly formed bone after distraction) we tested the effect of locally applied transforming growth factor beta 1 on distraction osteogenesis. A total of 28 mature female white New zealand rabbits weighing 3,5 kg-4,5 kg were studied. 10 animals were belonging to biomechanical testing group ( 5 for the study and 5 for the control subgroups), and the others were to histology group. In biomechanical group after tibial ostetomy TGF-beta 1 was applied subperiosteally for 5 days just proximal to osteotomy site. Control group received only the solvent. Seven days after tibial osteotomy distraction was started at a rate of 0.25mm/12 hours for 3 weeks with a unilateral fixator. Rabbits were sacrified at the end of a consodilation period 8 week after tibial osteotomy. We assessed density of the elongation zone of rabbit tibial bones with the computed tomography. Then biomechanical parametres were assessed using the torsional testing using the material testing machine. In histology group rabbits were classified as control and study ( rabbits that were given TGF-beta 1). Rabbits were sacrified at the end of first week, second week and fourth week also at the end of consolidation period 8 week after tibial osteotomy. Immunohistochemical and histologic parameters were examined. Biomechanical testing was applied as tortional testing. These values are used in determination of maximal loading, stiffness and energy absorbed during testing (brittlenes). The histomorphometric examination looked for the differences between the study and control groups in terms of bone formation pattern, bone quality and quantity. The immunohistochemical studies investigated the mechanism of TGF-beta 1, and it's presence in different cell types. The results of this study suggest that locally applied TGF-beta 1 improves the mineral density of distraction gap and load to failure( energy absorbed during testing). Though there is no significant histomorphometric difference between the study and control groups, there is an increased bone mineral density and an according maximum energy absorbance in the study group. This effect can be explained by the following mechanism: TGF-beta 1 exerts it's effect on two different receptor types ( Type 1 and 2). Type 1 receptors are localized to bone matrix and type 2 receptors are localized to the intracellular space. The specific stains utilized in the current experiment are specific to type 2 receptors. They have been shown to be down-regulated by exogenous TGF-beta 1 injections. Most probably, type 1 receptors are up-regulated by this exogenous administration, but unfortunately, there is currently no specific stain on tha market to display type 1 receptors and to prove this explanation.
Keywords: GROWTH-FACTOR-BETA; TRANSFORMING GROWTH-FACTOR-BETA-1; TGF-BETA; STIMULATION; EXPRESSION